Supervision and Effort in an Intertemporal Efficiency Wage Model: The Role of the Solow Condition - Jo\~ao Ricardo Faria (University of Kent, Department of Economics, 1998)
The Solow condition is examined in an intertemporal model that blends the shirking and the turnover models of efficiency wages with managerial supervision. It is shown that the Solow condition does not hold when shirking and turnover costs are considered. The Solow condition can be a possible outcome when managerial productivity offsets shirking and turnover costs.
Keywords: J50; J41; J63; J64; 330; Labour-Management Relations; Efficiency Wages; Unemployment; Turnover; Betriebsklima; Effizienzlohn; Theorie